The Analysis of Manager Competencies - Performance of Village-Owned Enterprises: The Village Government's Role as Mediator - Haryadi, Bambang; Latifah, Lyna; Anggraini, Merrie Satya (Institut Teknologi dan Bisnis Asia Malang, 2025)
The study aimed to analyze the role of village government in improving the competence of BUMDes managers and performance. Additionally, it looks at how village government functions as a mediator between manager competency and performance. A total of 100 data points were obtained from BUMDes around Madura and Malang Raya. Descriptive analysis was used to describe the characteristics of respondents. Multiple linear regression analysis to test the effect and moderation analysis with the moderated regression analysis technique to test the role of village government moderating the relationship between manager competence and performance. Conclusion: the role of village government has a positive effect on improving performance. Competence has a positive and significant effect on performance. The role of village government has a positive effect on the competence of managers. The village government is able to mediate the effect of manager competency on performance.